Explanatory handbook on the code of practice for reinforced concrete as recommended by the Reinforced Concrete Structures Committee of the Building Research Board - Scott, William L. (Concrete series., 1939)
For engineers, contractors and others using the Code of Practice for the use of Reinforced Conrete in Buildings, this book explains the clauses, advises on their interpretation and provides additional information of service.